Automated Evaluation of C-ITS Message Content for Enhanced Compliance and Reliability - Zdeněk Lokaj; Miroslav Vaniš; Radek Holý; Martin Šrotýř; Martin Zajíček; Shih-Chia Huang (Applied Sciences)
In the field of Cooperative Intelligent Transport Systems (C-ITSs), the traditional approach to testing often emphasizes technological parameters, leaving the validation of message content insufficiently addressed. Since the content of these messages is crucial for the correct functioning of C-ITS, this article demonstrates the potential for automated evaluation of C-ITS message content against relevant standards. It leverages our novel tools, Karlos and C-ITS SIM, to facilitate this process. Through detailed laboratory testing and data analysis, the study showcases the effectiveness of these automated solutions in enhancing the accuracy and reliability of message content validation.